2016
DOI: 10.1371/journal.pone.0167817
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Tone Regulation Induced by C-Type Natriuretic Peptide: Differences in Endothelium-Dependent and -Independent Mechanisms Involved in Normotensive and Spontaneously Hypertensive Rats

Abstract: Given that the role of C-type natriuretic peptide (CNP) in the regulation of vascular tone in hypertensive states is unclear, we hypothesized that impaired response of the nitric oxide system to CNP in spontaneously hypertensive rats (SHR) could affect vascular relaxation induced by the peptide in this model of hypertension, and that other endothelial systems or potassium channels opening could also be involved. We examined the effect of CNP on isolated SHR aortas, and the hindlimb vascular resistance (HVR) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…In human arteries, both GIRK and large conductance calcium-activated K + channels (BK Ca channels) have been implicated in CNP-evoked vasodilation [79]. Alternatively, studies in rats have shown that NPR-C can also couple to eNOS, resulting in the production of nitric oxide, although, this mechanism has only been reported in larger diameter vessels [81,82].…”
Section: Cnp Regulates Vascular Tone and Blood Pressurementioning
confidence: 99%
“…In human arteries, both GIRK and large conductance calcium-activated K + channels (BK Ca channels) have been implicated in CNP-evoked vasodilation [79]. Alternatively, studies in rats have shown that NPR-C can also couple to eNOS, resulting in the production of nitric oxide, although, this mechanism has only been reported in larger diameter vessels [81,82].…”
Section: Cnp Regulates Vascular Tone and Blood Pressurementioning
confidence: 99%
“…18,20) Iberiotoxin, a specific BKCa channel blocker, partly inhibited the vasorelaxant responses evoked by CNP in human penile resistance arteries 18) and rat aorta. 20) Furthermore, in patch-clamp studies in porcine coronary arterial smooth muscle cells, CNP enhanced the amplitude of the BKCa channel current, directly demonstrating that the opening of BKCa channels of vascular smooth muscle contributed to CNP-mediated relaxations. 21) These studies accord with ours findings in human gastroepiploic arteries.…”
Section: Discussionmentioning
confidence: 97%
“…ANP restores the attenuated cardioprotective effects in diabetic hearts, possibly due to the increase in endothelial nitric oxide synthesis (eNOS) expression and subsequent increase in NO activity 27 . Moreover, CNP induces vascular relaxation by endothelium-dependent and endothelium-independent mechanisms 28,29 . Although more precise human studies are required, the interaction left circumflex coronary artery; RCA, right coronary artery; LMT, left main trunk; VD, vessel disease; LVEF, left ventricular ejection fraction; LVEDP, left ventricular end-diastolic pressure; CI, cardiac index; SBP, systolic blood pressure; DBP, diastolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%